2018
DOI: 10.1016/j.scitotenv.2017.12.139
|View full text |Cite
|
Sign up to set email alerts
|

Air quality modelling in Catalonia from a combination of solar radiation, surface reflectance and elevation

Abstract: A new approach was conceived to model air quality in the region of Catalonia.• The proposed methodology combined geoprocessing tools and multivariate statistics. • Air quality was predicted from solar radiation, surface reflectance and elevation.• The results provided highly accurate predictions of air quality at ungauged zones. • The presence of irradiated built-up areas was found to endanger air quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Flood risk was one of the main priorities in the Plan, identifying and delimiting eight hotspots according to the road network of the city (Ayuntamiento de Santander, ), which were prioritised based on the vulnerable elements and consequences associated with them. In line with previous studies involving areas of influence to model urban phenomena (Jato‐Espino, Castillo‐Lopez, Rodriguez‐Hernandez, & Ballester‐Muñoz, ; van Hove et al, ), buffer areas of 250 m were delimited around the roads indicated in the Plan to represent these hotspots. Figure shows the position of these buffer areas throughout the city, including the streets, avenues, plazas, roundabouts, and tunnels contained in them.…”
Section: Methodsmentioning
confidence: 57%
“…Flood risk was one of the main priorities in the Plan, identifying and delimiting eight hotspots according to the road network of the city (Ayuntamiento de Santander, ), which were prioritised based on the vulnerable elements and consequences associated with them. In line with previous studies involving areas of influence to model urban phenomena (Jato‐Espino, Castillo‐Lopez, Rodriguez‐Hernandez, & Ballester‐Muñoz, ; van Hove et al, ), buffer areas of 250 m were delimited around the roads indicated in the Plan to represent these hotspots. Figure shows the position of these buffer areas throughout the city, including the streets, avenues, plazas, roundabouts, and tunnels contained in them.…”
Section: Methodsmentioning
confidence: 57%
“…A partir de la ecuación [1] se especifica un modelo econométrico general para estimar las cinco regresiones que componen el análisis: lnCC t =α 0 + α 1 ln Msost t + α2 ln PV CFOSt-1 + α 3 lnTemp t + DumA 1-3 + e t [2] La única variable rezagada en el tiempo es la proxy del parque vehicular, el consumo de gasolina y diésel de los vehículos es lento y tiene un efecto en el tiempo. Los datos de contaminación del aire están referidos en términos de emisiones en partículas y gases (ppm y mg/m3) en lugar de utilizar un índice de calidad de aire como hacen otros estudios (Jato- Espino et al, 2018;Xiao et al, 2020). Para el caso mexicano el uso de este índice subestima el efecto de la contaminación.…”
Section: Estrategia Empírica: Elección De La Técnica Y Especificación...unclassified
“…The forecasting of air quality became popular, many methods have been purposed for forecasting air quality such as hidden Markov model [15], first-order and one-variable grey model [16], developed support vector machine [17], fuzzy time series model [18][19] [25], Solar Radiation [26], and Fuzzy-AHP [27].…”
Section: Related Workmentioning
confidence: 99%